Early evidence for opposing effects of full versus fragmented adiponectin on melanogenesis in human epidermal melanocytes. (17th September 2018) - Tobin, D.J.
Abstract : Linked Article: Kim et al. Br J Dermatol 2018;179 :689–701 .